Predictive value of De Ritis ratio in metastatic renal cell carcinoma treated with tyrosine-kinase inhibitors - Janisch, Florian; Klotzbücher, Thomas; Marks, Phillip; Kienapfel, Christina; Meyer, Christian P; Yu, Hang; Fühner, Constantin; Hillemacher, Tobias; Mori, Keiichiro; Mostafei, Hadi; Shariat, Shahrokh F; Fisch, Margit; et al. (World journal of urology, 2021)
BACKGROUND: Predictive markers can help tailor treatment to the individual in metastatic renal cell carcinoma (mRCC). De Ritis ratio (DRR) is associated with oncologic outcomes in various solid tumors. OBJECTIVE: To assess the value of DRR in prognosticating survival in mRCC patients treated with tyrosine-kinase inhibitors (TKI). METHODS: Overall, 220 mRCC patients treated with TKI first-line therapy were analyzed. An optimal cut-off point for DRR was determined with Youden's J. We used multiple strata for DRR, performed descriptive, Kaplan-Meier and multivariable Cox-regression analyses to assess associations of DRR with progression-free (PFS) and overall survival (OS). RESULTS: Patients above the optimal cut-off point for DRR of ≥ 1.58 had fewer liver metastases (p = 0.01). There was no difference in PFS (p > 0.05) between DRR groups. DRR above the median of 1.08 (HR 1.42; p = 0.03), DRR ≥ 1.1(HR 1.44; p = 0.02), ≥ 1.8 (HR 1.56; p = 0.03), ≥ 1.9 (HR 1.59; p = 0.02) and ≥ 2.0 (HR 1.63; p = 0.047) were associated with worse OS. These associations did not remain after multivariable adjustment. In the intermediate MSKCC group, DRR was associated with inferior OS at cut-offs ≥ 1.0 (HR 1.78; p = 0.02), ≥ 1.1 (HR 1.81; p = 0.01) and above median (HR 1.88; p = 0.007) in multivariable analyses. In patients with clear-cell histology, DRR above median (HR 1.54; p = 0.029) and DRR ≥ 1.1 (HR 1.53; p = 0.029) were associated with OS in multivariable analyses. CONCLUSION: There was no independent association between DRR and survival of mRCC patients treated with TKI in the entire cohort. However, OS of patients with intermediate risk and clear-cell histology were affected by DRR. DRR could be used for tailored decision-making in these subgroups.
Keywords: sorafenib; Predictive Value of Tests; Male; Female; prognóza; Middle Aged; cytoredukční chirurgie; Sulfonamides; pyrimidiny; Neoplasm Staging; Alanine Transaminase; nefrektomie; inhibitory proteinkinas; Prognosis; stupeň nádoru; Survival Analysis; alanintransaminasa; mužské pohlaví; Carcinoma, Renal Cell; Kidney Neoplasms; ženské pohlaví; staging nádorů; Pyrimidines; analýza přežití; Nephrectomy; karcinom z renálních buněk; Cytoreduction Surgical Procedures; Karnofského skóre; prediktivní hodnota testů; Indazoles; indazoly; Protein Kinase Inhibitors; sunitinib; Neoplasm Grading; Karnofsky Performance Status; sulfonamidy; Sorafenib; lidé středního věku; Aspartate Aminotransferases; aspartátaminotransferasy; nádory ledvin; lidé; Humans; Sunitinib